Genetic variation in Hyperpolarization-activated cyclic nucleotide-gated channels and its relationship with neuroticism, cognition and risk of depression - Mcintosh, Andrew M. (Frontiers in Genetics, 2012)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels are encoded by four genes (HCN1-4) and, through activation by cyclic AMP (cAMP), represent a point of convergence for several psychosis risk genes. On the basis of positive preliminary data, we sought to test whether genetic variation in HCN1-4 conferred risk of depression or cognitive impairment in the Generation Scotland: Scottish Family Health Study. HCN1, HCN2, HCN3 and HCN4 were genotyped for 43 haplotype-tagging SNPs and tested for association with DSM-IV depression, neuroticism and a battery of cognitive tests assessing cognitive ability, memory, verbal fluency and psychomotor performance. No association was found between any HCN channel gene SNP and risk of depression, neuroticism or on any cognitive measure. The current study does not support a genetic role for HCN channels in conferring risk of depression or cognitive impairment in human subjects within the Scottish population.